Study on the Relationship of Root Morphology and Phosphorus Absorption Efficiency With Phosphorus Uptake Capacity in 235 Peanut (Arachis hypogaea L.) Germplasms - Zhu, Suqing; Luo, Lu; Zhang, Xiurong; Zhao, Meiyu; Wang, Xiaoqian; Zhang, Junjie; Wan, Qian; Li, Xianrong; Wan, Yongshan; Zhang, Kun; Liu, Fengzhen (Frontiers in Environmental Science, 2022)
Peanut (Arachis hypogaea L.) is a significant oil and protein crop. Its yields greatly depend on the availability of phosphorus (P). Root morphology and P absorption efficiency are important factors affecting the P uptake capacity, but their relationships in peanuts are rarely reported. Here, we report the effect of root morphology and P absorption efficiency on the P uptake capacity in peanuts using 235 germplasms. In this work, we use the P uptake rate per plant to reflect the P uptake capacity. The P uptake capacity was significantly increased after low-P treatment and showed great differences among the germplasms. The germplasms with higher P absorption efficiency and a well-developed root system have higher P uptake capacity. Under both P conditions, the P absorption efficiency plays more important roles than root morphology in P uptake capacity, and the P uptake rate per unit root dry weight and the P uptake rate per unit root surface area contributed the most. Root morphology contributes more to the P uptake capacity under low-P treatment than under sufficient-P conditions, and root surface area contributed the most. Forty-eight germplasms with higher P uptake capacity were screened, and they had three different uptake strategies under low-P treatment. These findings indicated that low-P stress induces root growth and improves the P absorption efficiency of peanuts to ensure the plant gets enough P; provides new insights into the relationship between the P uptake capacity, P absorption efficiency, and root morphology; and furnishes important evaluation indexes for high P-efficient germplasm selection.